An aggregation-induced emission (AIE)-active fluorescent chemodosimeter for selective sensing of hypochlorite in water and solid state: Endogenous detection of hypochlorite in live cells. (December 2021) - Samanta, Sandip Kumar; Maiti, Kalipada; Manna, Saikat Kumar; Ali, Syed Samim; Guria, Uday Narayan; Ghosh, Aritri; Datta, Pallab; Mahapatra, Ajit Kumar
Abstract: Hypochlorite (ClO − ) being an important reactive oxygen species plays a crucial role in the oxidative damage to tissue and other various diseases. Highly selective, sensitive, and quick detection of aberrant ClO − is vital for the protection of living organisms and the environment. Accordingly, fluorescent molecules are most effective sensor system for ClO − . Herein, we have synthesized and characterized a water soluble AIE-active tetraphenylethylene (TPE)-based fluorescent molecule TPE−Py + (TPP ) for rapid (10 s) and selective detection of ClO − based on ClO − induced oxidation of N-alkylpyridinium to N-methyl-2-pyridone. ClO − mediated aggregation-induced emission (AIE) enhancement corresponds to turn-on response. Scanning electron microscopic (SEM) study supports AIE behavior of the probe upon treatment with ClO − . The detection limit of TPP for ClO − was found to be 8.89 nM and exhibited high selectivity among other possibly interfering analytes (ROS, RNS, other ions). TPP -based handy test kits were developed for the solid-state detection of ClO − in environmental samples. Furthermore, our probe was effective in detecting ClO − in real water samples, fetal bovine serum and able to detect endogenous ClO − in live cell. Graphical abstract: Image 1 Highlights: We have reported an AIE-active "turn-on" fluorescent chemodosimeter TPP for the detection of ClO − . Probe shown quick reaction time, high selectivity towards ClO − over other competing analytes. The probe can distinguish between cancer cells and normal animal cells quite efficiently. TPP-based test kits were developed for the solid-state detection of ClO − in environmental samples. The probe TPP is very much effective for quantitative detection of ClO − in different real water samples and in fetal bovine serum.